Attitude towards and factors affecting uptake of population‐based BRCA testing in the Ashkenazi Jewish population: a cohort study. (18th March 2019) - Manchanda, R; Burnell, M; Gaba, F; Sanderson, S; Loggenberg, K; Gessler, S; Wardle, J; Side, L; Desai, R; Brady, AF; Dorkins, H; Wallis, Y; et al.
Abstract : Objective: To evaluate factors affecting unselected population‐based BRCA testing in Ashkenazi Jews (AJ). Design: Cohort‐study set within recruitment to the GCaPPS trial (ISRCTN73338115). Setting: North London AJ population. Population or sample: Ashkenazi Jews women/men >18 years, recruited through self‐referral. Methods: Ashkenazi Jews women/men underwent pre‐test counselling for BRCA testing through recruitment clinics (clusters). Consenting individuals provided blood samples for BRCA testing. Data were collected on socio‐demographic/family history/knowledge/psychological well‐being along with benefits/risks/cultural influences (18‐item questionnaire measuring 'attitude'). Four‐item Likert‐scales analysed initial 'interest' and 'intention‐to‐test' pre‐counselling. Uni‐ and multivariable logistic regression models evaluated factors affecting uptake/interest/intention to undergo BRCA testing. Statistical inference was based on cluster robust standard errors and joint Wald tests for significance. Item‐Response Theory and graded‐response models modelled responses to 18‐item questionnaire. Main outcome measures: Interest, intention, uptake, attitude towards BRCA testing. Results: A total of 935 individuals (women = 67%/men = 33%; mean age = 53.8 (SD = 15.02) years) underwent pre‐test genetic‐counselling. During the pre‐counselling, 96% expressed interest in and 60% indicated a clear intention to undergo BRCA testing. Subsequently, 88% opted for BRCA testing. BRCA ‐related knowledge ( P  = 0.013) and degree‐level education ( P  = 0.01) were positively and negatively (respectively) associated with intention‐to‐test. Being married/cohabiting had four‐fold higher odds for BRCA testing uptake ( P  = 0.009). Perceived benefits were associated with higher pre‐counselling odds for interest in and intention to undergo BRCA testing. Reduced uncertainty/reassurance were the most important factors contributing to decision‐making. Increased importance/concern towards risks/limitations (confidentiality/insurance/emotional impact/inability to prevent cancer/marriage ability/ethnic focus/stigmatisation) were significantly associated with lower odds of uptake of BRCA testing, and discriminated between acceptors and decliners. Male gender/degree‐level education ( P  = 0.001) had weaker correlations, whereas having children showed stronger ( P  = 0.005) associations with attitudes towards BRCA testing. Conclusions: BRCA testing in the AJ population has high acceptability. Pre‐test counselling increases awareness of disadvantages/limitations of BRCA testing, influencing final cost‐benefit perception and decision‐making on undergoing testing. Tweetable abstract: BRCA testing in Ashkenazi Jews has high acceptability and uptake. Pre‐test counselling facilitates informed decision‐making. Tweetable abstract: BRCA testing in Ashkenazi Jews has high acceptability and uptake. Pre‐test counselling facilitates informed decision‐making. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights15654